History & Evolution of Shadachakra – A Review of Literature. - Kaur, Smriti; Rani, Seema (International Research Journal of Ayurveda & Yoga, 2023)
Popular is the term shadachakra which literally originated from two words, shad is representing numerical value six and chakra is wheel or circle which are basically the centres of consciousness which channelize the human potential energy. But the number and description are different according to different philosophies and tantras. The concept took origin from Rigveda, and then the Upanishads (especially yoga Upanishad which are 17 in number) put a light on it. The concept is more related to tantra shastra than yoga. So yogic classical text (except Shiva Samhita) does not mention it in systematized format. Buddhist texts have some different description. Sat- chakra Nirupana is 15th century classical Sanskrit text which describes the chakra in the way we know it today. Christopher Hills correlates it with rainbow body and also mentioned the scientific explanation for the same. This is a review article on history and evolution of shadachakra with brief description of literature present on it both classical as well as modern books. And surely this effort will help to recollect the knowledge of chakra dispersed in various text easily.